Challenging Androcentrism: The Beginnings of Editorial Tegualda - Meza, Andrea (RChD: creación y pensamiento, 2023)
Gender studies have alerted us to how knowledge has historically been produced and validated from an androcentric perspective, devaluing and rendering invisible certain groups of people as knowledge generators. Given that there are still gaps in the field of book publishing that require attention, we invite reflection on the relationship of women with the Chilean publishing industry, focusing on the experience of Editorial Tegualda (1945-1950), a publishing label founded by writer Gladys Thein and Graciela Marín Urzúa. From a feminist perspective, considering both discourse and visuality, our work focuses on reviewing texts written by both publishers, photographs, illustrations, interviews, and testimonials from individuals with whom they established emotional and collaborative ties. By paying attention to the voices of the protagonists, our intention is to contribute to the validation of women’s experiences, recognizing their diversity and their ability to create design objects and generate knowledge within the framework of their practices.